KEKERASAN SEKSUAL KYAI TERHADAP SANTRI PEREMPUAN DI PESANTREN - Bz. Fitri Pebriaisyah; Wilodati Wilodati; Siti Komariah (Kafa`ah: Journal of Gender Studies, 2022)
This paper discusses the practice of sexual violence perpetrated by religious leaders (kyai) against female students in Islamic boarding schools. Using the literature review research method, the researcher dissects the pattern that is often used by kyai in committing sexual violence, how it impacts, and how preventive measures can be taken. The results of this study show that there are two general patterns used by kyai as a tool to commit sexual violence in Islamic boarding schools. The first is the existence of a patriarchal culture that is eternal and has been institutionalized in the pesantren environment. Second, there is an unequal power relationship between the kyai and the santri. The impact experienced is to suffer physically, psychologically, theologically, and sociologically. Therefore, a gender mainstreaming program is needed to create a gender-sensitive and responsive pesantren through sexual education that is integrated into the pesantren curriculum which emphasizes awareness of gender issues and increases awareness for students as a preventive measure against sexual violence in pesantren.